2017
DOI: 10.5144/0256-4947.2017.144
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry of Arabian nose using computed tomography scanning

Abstract: BACKGROUNDThe nose plays a critical role in determining the external appearance of an individual. We studied the craniofacial anthropometrics by CT scanning since previous studies in the field were conducted in Saudi populations using photometric analysis.OBJECTIVESObtain objective and quantitative data that can help surgeons plan cosmetic procedures for the nose.DESIGNA cross-sectional analytical study.SETTINGDepartment of Otorhinolaryngology, Head and Neck Surgery, King Abdulaziz University Hospital, King Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In contrast, the nasal tip angle/nasal tip protrusion in Saudi adults is significantly smaller than in other ethnicities [23]. These differences in facial anthropometrics with other ethnicities were consistent in some studies [25,26,30,31] that concluded differences in ethnic groups and that facial norms and measurements of other Caucasian populations cannot be applied to the Arab population. This distinction has a great impact on treatment planning for corrective, reconstructive, and orthognathic procedures.…”
Section: Facial Anthropometricssupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, the nasal tip angle/nasal tip protrusion in Saudi adults is significantly smaller than in other ethnicities [23]. These differences in facial anthropometrics with other ethnicities were consistent in some studies [25,26,30,31] that concluded differences in ethnic groups and that facial norms and measurements of other Caucasian populations cannot be applied to the Arab population. This distinction has a great impact on treatment planning for corrective, reconstructive, and orthognathic procedures.…”
Section: Facial Anthropometricssupporting
confidence: 77%
“…Several studies were conducted to assess Saudi facial anthropometry [22][23][24][25][26][27][28][29][30] that are essential for facial reconstructive procedures [25] and has many practical applications, including classification, diagnosis, and treatment of craniofacial anomalies, evaluation and treatment of post-traumatic deformities [29]. A study including 209 Saudi adults reported that nasal widths lie between Whites and Chinese.…”
Section: Facial Anthropometricsmentioning
confidence: 99%
“…For an exocanthion landmark, the marker was positioned on the frontozygomatic suture, a number of millimeters lateral from the actual landmark, as shown in detail by Ferrario et al 31 Physical and social characteristics must be taken into account in order to perform rhinoplasty in the Middle Eastern population. [33][34] The ability of CT scans in making a pre-operative plan for rhinoplasty patients is not excessive. Clinical series of CT-PNS data were used to find unique radiological features of the native Saudi nose and the results for the Saudi population were compared with the Asian community.…”
Section: Discussionmentioning
confidence: 99%
“…When considering that the nose plays a critical role in determining the external appearance of an individual, in [40], researchers studied the craniofacial anthropometrics by CT scanning, providing objective and quantitative data that can help surgeons to plan cosmetic procedures for the nose. Another study [41], established and reported normal anthropometric orbital measurements in a pediatric population using fine-cut craniofacial CT.…”
Section: Anthropometry and Simulationmentioning
confidence: 99%